2012
DOI: 10.4049/jimmunol.1102859
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Natural Autoantibodies in MRL-lpr Mice Protects from Lupus Nephritis and Improves Survival

Abstract: Natural autoantibodies (NAA) and their associated B cells constitute a substantial proportion of the normal Ab and B cell repertoire. They often have weak reactivity toward a variety of self-Ags such as DNA, nucleoproteins, and phospholipids. It remains controversial whether NAA contribute to or protect from autoimmune diseases. Using site-directed transgenic (sd-tg) mice expressing a prototypic NAA, we investigated the effect of NAA and NAA-producing B cells in disease development in the autoimmune-prone MRL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 89 publications
1
38
0
Order By: Relevance
“…As has been pointed out elsewhere, autoreactivity can also be protective, as is the case for many natural antibodies (NA) which may ameliorate autoimmunity (51, 52) and help maintain homeostasis (51). IgM NA are often positively charged to facilitate interaction with negatively charged targets (53), and may have high levels of poly-reactivity (54).…”
Section: Discussionmentioning
confidence: 88%
“…As has been pointed out elsewhere, autoreactivity can also be protective, as is the case for many natural antibodies (NA) which may ameliorate autoimmunity (51, 52) and help maintain homeostasis (51). IgM NA are often positively charged to facilitate interaction with negatively charged targets (53), and may have high levels of poly-reactivity (54).…”
Section: Discussionmentioning
confidence: 88%
“…Recent reports describe a role of low-affinity self-reactive antibodies in the maintenance of immune homeostasis. 16,17 If this would be the case for FVIII-binding antibodies found in healthy individuals, these antibodies might be involved in the maintenance of peripheral immune tolerance against FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Furthermore, recent studies of self-reactive antibodies in healthy individuals indicated that these antibodies might be involved in the maintenance of immune homeostasis. 16,17 Gilles et al and others reported that the antibody response to FVIII in patients is not isotypically restricted and involves all IgG subclasses with a preponderance of IgG1 and IgG4. 18 Only limited information is available on the characteristics of antibodies against FVIII which are found in patients without FVIII inhibitors and in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In view of recent studies indicating immunoregulatory properties of IgM (51–54) we determined whether transferred Ars/A1 B cells produced IgM a (Fig. 6C).…”
Section: Resultsmentioning
confidence: 99%